Are new variants of psoriasis therapy (IL‐17 inhibitors) safe? - Wcisło‐Dziadecka, Dominika; Kaźmierczak, Agata; Grabarek, Beniamin; Zbiciak‐Nylec, Martyna; Brzezińska‐Wcisło, Ligia (International journal of dermatology, 2019)
Psoriasis is a chronic, recurrent, inflammatory, and proliferative skin disease. Its etiology has not yet been fully assessed, but undoubtedly it is a multifaceted disease. The key role in its pathomechanism is played by genetic, immunologic, and environmental factors and stress. If traditional methods of psoriasis treatment (phototherapy, methotrexate, retinoids, cyclosporine A) fail, we reach for the following biopharmaceuticals – infliximab, etanercept, adalimumab, or ustekinumab. However, genetic engineering progress discovers new possibilities – the pending clinical trials involve IL‐17, IL‐23 antagonists, PDE4 and ‐3 and ‐1. Psoriasis etiopathogenesis mainly involves the IL‐17A, IL‐17F, and IL‐17A/F subtypes, which affect the keratinocytes. The biological therapy molecularly oriented with the antagonists of interleukin 17 is based mainly on the influence onto the cytokine in the manner that prevents it from binding with the receptor. Three biopharmaceuticals are currently under third phase studies: two fully humanized antibodies neutralizing IL‐17 – ixekizumab and secukinumab, and one human monoclonal antibody, brodalumab. The below work will be devoted to the analysis of possible undesirable symptoms, which were observed during the studies. We will try to review the latest literature concerning the most important clinical trials conducted in many centers.